SAT0368 PREGNANCY IN WOMEN WITH SPONDYLOARTHRITIS: WHO ARE THE PATIENTS AT RISK OF DISEASE FLARE?. (2nd June 2020) - Crisafulli, F.; Cruz-Machado, A. R.; Gerardi, M. C.; Filippini, M.; Fredi, M.; Gorla, R.; Lazzaroni, M. G.; Nalli, C.; Taglietti, M.; Lojacono, A.; Zanardini, C.; Zatti, S.; et al.
Abstract : Background: Patients with Spondyloarthritis (SpA) can experience flares during pregnancy and postpartum even though the available data are limited and not conclusive. Objectives: To assess disease activity and treatment modification during pregnancy and postpartum in patients with SpA and to identify risk factors for disease flare. Methods: Data on SpA pregnancies prospectively-followed in a pregnancy clinic from 2010 to 2019 were retrospectively analysed. Disease activity was assessed during each trimester and postpartum using ASDAS-CRP or DAS28-CRP. Flare was defined as an increase of disease activity leading to treatment modification (introduction or increase ≥5mg/day of prednisone, introduction of cDMARD or bDMARD) 1 . Results: Data on 50 pregnancies in 46 patients were collected (mean age at conception 33±4.7 years; median disease duration: 60 months (IQR 24-132); 33 psoriatic arthritis, 6 axialSpA, 2 reactive arthritis, 2 IBD-related SpA; 6 undifferentiated SpA, 1 juvenile idiopathic arthritis). Six pregnancies ended in miscarriage, so they weren't considered for the analysis of flares during pregnancy (table 1 ). Fifteen out of 44 (34%) pregnancies had at least one flare during pregnancy (6, 7 and 4 during 1 st, 2 nd and 3 rd trimester respectively; 2 pregnancies had multiple flares). A higher rate of flare was observed in pregnancies of patients with axial involvement (p=0.01), on treatment with bDMARDs at preconceptional visit (p=0.03) and who stopped TNFi at positive pregnancy test (p=0.03). Peripheral involvement was associated with a lower rate of flares (p=0.02). Medications resumed during pregnancy were steroids (in 6 pregnancies), cDMARDs (2 sulfasalazine, 1 cyclosporine) and bDMARDs (4 certolizumab, 4 etanercept). During postpartum period flares were recorded in 46% of patients. Conclusion: In our cohort of prospectively-followed SpA pregnancies, 34% experienced a flare during pregnancy and 46% during postpartum. Flares occurred especially in those patients who discontinued TNFi early in pregnancy and with axial involvement. When resumed during pregnancy, TNFi was able to control the disease. At preconception counselling, the continuation of TNFi during pregnancy should be considered to ensure a better control of disease. References: [1]Fischer-Betz R et al.Arthritis Rheumatol. 2015; 67. Disclosure of Interests: None declared